Rapamycin-mediated mTOR inhibition uncouples HIV-1 latency reversal from cytokine-associated toxicity - Alyssa R. Martin; Ross A. Pollack; Adam Capoferri; Richard F. Ambinder; Christine M. Durand; Robert F. Siliciano (The Journal of Clinical Investigation, 2017)
Current strategies for HIV-1 eradication require the reactivation of latent HIV-1 in resting CD4+ T cells (rCD4s). Global T cell activation is a well-characterized means of inducing HIV-1 transcription, but is considered too toxic for clinical applications. Here, we have explored a strategy that involves a combination of immune activation and the immunosuppressive mTOR inhibitor rapamycin. In purified rCD4s from HIV-1–infected individuals on antiretroviral therapy, rapamycin treatment downregulated markers of toxicity, including proinflammatory cytokine release and cellular proliferation that were induced after potent T cell activation using αCD3/αCD28 antibodies. Using an ex vivo assay for HIV-1 mRNA, we demonstrated that despite this immunomodulatory effect, rapamycin did not affect HIV-1 gene expression induced by T cell activation in these rCD4s. In contrast, treating activated rCD4s with the immunosuppressant cyclosporin, a calcineurin inhibitor, robustly inhibited HIV-1 reactivation. Importantly, rapamycin treatment did not impair cytotoxic T lymphocyte (CTL) recognition and killing of infected cells. These findings raise the possibility of using rapamycin in conjunction with T cell–activating agents in HIV-1 cure strategies.